Cell voltage versus electrode potential range in aqueous supercapacitors - Dai, Zengxin; Peng, Chuang; Chae, Jung Hoon; Ng, Kok Chiang; Chen, George Z. (Nature Publishing Group, 2015)
Supercapacitors with aqueous electrolytes and nanostructured composite electrodes are attractive because of their high charging-discharging speed, long cycle life, low environmental impact and wide commercial affordability. However, the energy capacity of aqueous supercapacitors is limited by the electrochemical window of water. In this paper, a recently reported engineering strategy is further developed and demonstrated to correlate the maximum charging voltage of a supercapacitor with the capacitive potential ranges and the capacitance ratio of the two electrodes. Beyond the maximum charging voltage, a supercapacitor may still operate, but at the expense of a reduced cycle life. In addition, it is shown that the supercapacitor performance is strongly affected by the initial and zero charge potentials of the electrodes. Further, the differences are highlighted and elaborated between freshly prepared, aged under open circuit conditions, and cycled electrodes of composites of conducting polymers and carbon nanotubes. The first voltammetric charging-discharging cycle has an electrode conditioning effect to change the electrodes from their initial potentials to the potential of zero voltage, and reduce the irreversibility.